Speed Trials Speed, Length of Approach Run and Speed Reduction in turns Effect of Wind on Speed - Verstelle, J. Th. (The International Hydrographic Review, 2015)
It is generally acknowledged that the length of straight approach runs for speed trials should be of the order of 3 to 3 1/2 nautical miles and that turns should be made at a rudder angle of 5°, As these figures will have been based on experience with ships that nowadays are considered relatively small (some 20 000 tons displacement or smaller) the question may be, and in some cases has been, raised as to whether the present-day very large tankers at their usual speed of about 17 knots might not require longer approach runs and/or smaller rudder angles for turning to the opposite course. This paper intends to give an answer to this question. Although the required information could up to now be collected for one ship only, the trial described in this paper indicates that for this particular ship — of 62 000 tons displacement and a speed of 17 knots — the answer to the question is negative.